2010
DOI: 10.1016/s1474-4422(10)70105-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology in adult gliomas: diagnostic, prognostic, and predictive markers

Abstract: Over the past 10 years, there has been an increasing use of molecular markers in the assessment and management of adult malignant gliomas. Some molecular signatures are used diagnostically to help pathologists classify tumours, whereas others are used to estimate prognosis for patients. Most crucial, however, are those markers that are used to predict response to certain therapies, thereby directing clinicians to a particular treatment while avoiding other potentially deleterious therapies. Recently, large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
194
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(199 citation statements)
references
References 97 publications
1
194
0
4
Order By: Relevance
“…Another study recently reported a similar finding and suggested that true genomic instability was the reason for shortened survival of patients with glioblastoma and complete 1p/19q co-deletion. 15 Furthermore, in the study of Gravendeel et al, 30 10 out of 175 glioblastoma cases showed complete 1p/19q co-deletion but no explicit correlations with overall survival for these 10 cases were made. However, most studies do not report this lack of favorable prognostic impact of 1p/19q codeletion in glioblastoma patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study recently reported a similar finding and suggested that true genomic instability was the reason for shortened survival of patients with glioblastoma and complete 1p/19q co-deletion. 15 Furthermore, in the study of Gravendeel et al, 30 10 out of 175 glioblastoma cases showed complete 1p/19q co-deletion but no explicit correlations with overall survival for these 10 cases were made. However, most studies do not report this lack of favorable prognostic impact of 1p/19q codeletion in glioblastoma patients.…”
Section: Discussionmentioning
confidence: 97%
“…Although one study suggested that complete 1p/19q co-deletion is associated with longer survival independent of pathological diagnosis, 14 others report that deletions involving 1p and 19q are uncommon in glioblastomas but predict a shortened survival. 15 Also, it has been suggested that complete 1p/19q co-deletion and IDH1 mutation should be considered incompatible with the diagnosis of glioblastoma. 16 Furthermore, a recent study reported that glioblastomas carrying IDH1 mutations are associated with a better survival than anaplastic astrocytomas without these mutations.…”
mentioning
confidence: 99%
“…Currently, the most relevant molecular markers in diagnostics of diffuse gliomas include 1p/19q deletion, MGMT promoter hypermethylation, and IDH1 mutation (Jansen et al, 2010;Riemenschneider et al, 2010;von Deimling et al, 2011). In this study, we have assessed associations between gene copy number changes by array CGH, methylation status of MGMT gene by pyrosequencing and IDH1 mutation status by immunohistochemistry in different glioma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Standard methods for 1p/19q testing are FISH and LOH assay by PCR (Jansen et al, 2010). However, FISH may not detect all deletions depending on which probes are used.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with this most aggressive glioma variant have a median survival of only 15 months (Wen et al, 2008). Over the past 10 years, there has been an increasing understanding of the molecular biology of gliomas, such as O-6-methylguanine-DNA methyltransferase (MGMT) methylation status, epidermal growth factor receptor (EGFR) pathway alterations, and isocitrate dehydrogenase (IDH) mutations, which have been determined to be diagnostic, prognostic, and predictive markers (Jansen et al, 2010).With the rapid development of systems biology, increasing numbers of key cancer genes and their correlated proteins have been identified using bioinformatics.…”
Section: Introductionmentioning
confidence: 99%